Journal Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Journal of Infrastructure & Facility Asset ManagementVolume 1, Issue 2, September 2019 (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.1, Issue 1, March 2019Preliminary Recognition of River Infrastructure Mahendra Andiek Maulana, Hitapriya Suprayitno & Ria Asih Aryani SoemitroReflection on Data Error Identification Methods for Field Survey Data on Commuter Train Passenger Travel Behavior Hitapriya Suprayitno & Ria Asih Aryani SoemitroGradation Analysis of Reclaimed Asphalt Pavement from National Road as Asphalt Concrete Layer Ari Widayanti, Ria Asih Aryani Soemitro, Januarti J. Ekaputri & Hitapriya SuprayitnoMental Tasks EEG Signal Classification Using Support Vector Machine Wahyu Caesarendra, Syahara U. Lekson & Muhammad AgungSearching the Appropriate Minimum Sample Size Calculation Method for Commuter Train Passenger Travel Behavior Survey Anita Susanti, Ria Asih Aryani Soemitro, Hitapriya Suprayitno & Vita Ratnasari